The Oncolytic herpes simplex virus type-1 (HSV-1) vaccine strain VC2 causes intratumor infiltration of functionally active T cells and inhibition of tumor metastasis and pro-tumor genes VEGF and PDL1 expression in the 4T1/Balb/c mouse model of stage four breast cancer - Nabi, Rafiq; Musarrat, Farhana; Menk P. Lima, Jose Cesar; Langohr, Ingeborg M.; Chouljenko, Vladimir N.; Kousoulas, Konstantin G. (Frontiers in Molecular Biosciences, 2023)
Introduction: Oncolytic viruses (OVs) provide new modalities for cancer therapy either alone or in combination with synergistic immunotherapies and/or chemotherapeutics. Engineered Herpes Simplex Virus Type-1 (HSV-1) has shown strong promise for the treatment of various cancers in experimental animal models as well as in human patients, with some virus strains licensed to treat human melanoma and gliomas. In the present study we evaluated the efficacy of mutant HSV-1 (VC2) in a late stage, highly metastatic 4T1 murine syngeneic. Method: VC2 was constructed VC2 using double red recombination technology. For in-vivo efficacy we utilized a late stage 4T1 syngeneic and immunocompetent BALB/cJ mouse model breast cancer model which exhibits efficient metastasis to the lung and other organs. Results: VC2 replicated efficiently in 4T1 cells and in cell culture, achieving titers similar to those in African monkey kidney (Vero) cells. Intra-tumor treatment with VC2 did not appreciably reduce average primary tumor sizes but a significant reduction of lung metastasis was noted in mice treated intratumorally with VC2, but not with ultraviolet-inactivated VC2. This reduction of metastasis was associated with increased T cell infiltration comprised of CD4+ and CD4+CD8+ double-positive T cells. Characterization of purified tumor infiltrating T cells revealed a significant improvement in their proliferation ability compared to controls. In addition, significant T cell infiltration was observed in the metastatic nodules associated with reduction of pro-tumor PD-L1 and VEGF gene transcription. Conclusion: These results show that VC2 therapy can improve anti-tumor response associated with a better control of tumor metastasis. improve T cell responses and reduce pro-tumor biomarker gene transcription. VC2 holds promise for further development as an oncolytic and immunotherapeutic approach to treat breast and other cancers.